Conflict management: a survey on style of behavior of FTMSK's lecturers / Siti Suzawati Sulaiman - Sulaiman, Siti Suzawati (2005)
Understanding conflict and making informed decisions in response to conflict is fundamental when seeking to build a strong development team in managing project. Different work groups within the FTMSK's lecturers can become entangled in conflict if they pursue different goals and objectives. The purpose of this study is to explore the lecturers' style of behavior and how these styles of behavior influence their conflict management style with their clique. A number of behavioral styles and conflict-handling style have been described in the literatures, however four behavioral styles were identified. These are analytical (thinking oriented), driving (action oriented), expressive (intuition oriented) and amiable (relationship oriented). Besides, five styles of handling conflict were also recognized. It consists of integrating, compromising, avoiding, dominating and obliging style. Findings fi-om the study could assist FTMSK's lecturers when they are building teams, encouraging creativity among teams, building group dynamics, exploring job satisfaction and examining work productivity.